New Approach of Integration Space-Ground: Hotspots, Challenges, and Key Technologies of Direct-to-Smartphone - Yuanzhi HE; Lingcai YANG; Yongwei XIAO; Shijie ZHANG; Zhiqiang LI; Yun LIU (天地一体化信息网络)
Direct-to-smartphone, as a potential technological means for achieving the integration of space and ground in the future, has received widespread attention from industry and academia.Compared with traditional satellite mobile communication, there are many challenges in the current direct-to-smartphone technology.The current development status and system architecture of two direct-to-smartphone technology routes based on synchronous orbit satellites and asynchronous orbit satellites were introduced, and the technical challenges from the air-interface side, satellite side, network side, and terminal side were summarized.Several solutions were proposed, included satellite-terrestrial synchronization, satellite-borne ultra-large array antenna, and satellite-terrestrial heterogeneous network roaming, providing technical support for the development of direct-to-smartphone technology.Finally, a brief outlook were provided.